Process cinema : handmade film in the digital age - MacKenzie, Scott, 1967-; Marchessault, Janine (McGill-Queen's University Press, 2019)
"Handmade films stretch back to cinema's beginnings, yet until now their rich history has been neglected. Process Cinema is the first book to trace the development of handmade and hand-processed film in its historical and contemporary contexts, and from a global perspective. Mapping the genealogy of handmade film, and uncovering confluences, influences, and interstices between various international movements, sites, and practices, Process Cinema positions the resurgence of handmade and process cinema as a counter-practice to the rise of digital filmmaking. This volume brings together a range of renowned academics and artists to examine contemporary artisanal films, DIY labs, and filmmakers typically left out of the avant-garde canon, addressing the convergence between the analog and the digital in contemporary process cinema. Contributors investigate the history of process cinema - unscripted, improvisatory manipulation of the physicality of film - with chapters on pioneering filmmakers such as Len Lye and Marie Menken, while others discuss an international array of collectives devoted to processing films in artist-run labs from South Korea to Finland, Australia to Austria, and Greenland to Morocco, along with historical and contemporary practices in Canada and the United States. Addressing the turn to a new, sustainable creative ecology that is central to handmade films in the twenty-first century, and one that defines today's reinvigorated film cultures, Process Cinema features some of the most beautiful handcrafted films and the most forward-thinking filmmakers within a global context."--